1969
DOI: 10.1017/s0043174500031350
|View full text |Cite
|
Sign up to set email alerts
|

Basis for Selectivity of Linuron on Carrot and Common Ragweed

Abstract: Both carrot (Daucus carota L.) and common ragweed (Ambrosia artemisiifolia L.) plants metabolized 3-(3,4-dichlorophenyl)-1-methoxy-1-methylurea (linuron). Traces of all of the following derivatives of linuron were detected in both plants: 3-(3,4-dichlorophenyl)-1-methoxyurea, 3-(3,4-dichlorophenyl)-1-methylurea, 3-(3,4-dichlorohenyl)urea, and 3,4-dichloroaniline. Differences in absorption and concentration of these derivatives were observed between carrot and ragweed plants. All of the above derivatives were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

1972
1972
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
2
6
0
4
Order By: Relevance
“…Common ragweed has also developed resistance to S-triazine herbicides such as atrazine, cloransulam-methyl, cyanazine, simazine, and many Group 2 herbicides (Heap 2004;Patzoldt et al 2001). Kuratle et al (1969) reported that common ragweed did not metabolize linuron into nontoxic derivatives as well as carrot, thus suggesting that the selectivity of this herbicide is due to differential metabolism. Both Oettmeier et al (1982) and Fuerst et al (1986) reported that the linuron resistance observed in some weed biotypes was due to an alteration of the herbicide binding site within the chloroplast, although Fuerst et al (1986) concluded that the biotypes used by the two research groups differed in the exact mutation that conferred resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Common ragweed has also developed resistance to S-triazine herbicides such as atrazine, cloransulam-methyl, cyanazine, simazine, and many Group 2 herbicides (Heap 2004;Patzoldt et al 2001). Kuratle et al (1969) reported that common ragweed did not metabolize linuron into nontoxic derivatives as well as carrot, thus suggesting that the selectivity of this herbicide is due to differential metabolism. Both Oettmeier et al (1982) and Fuerst et al (1986) reported that the linuron resistance observed in some weed biotypes was due to an alteration of the herbicide binding site within the chloroplast, although Fuerst et al (1986) concluded that the biotypes used by the two research groups differed in the exact mutation that conferred resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Diverse role of a microbial Cytochrome P450 BM3 has been exploited for the production of unusual oxymolecules because this type of P450 is reported with the maximal activity of monooxygenase out of all P450s [41]. [44]. Improved herbicide metabolism was observed with the expression of Cytochrome P45076B1 both in tobacco and Arabidopsis carrying a 20-fold increase in tolerance to linuron as well as some other selected phenylureas [45].…”
Section: Figurementioning
confidence: 99%
“…This pathway comprises the conversion of S-reticuline from the feedstock of sugar with the help of reticuline epimerase which is a complex protein consisting various modules i.e., P450 CYP82Y2 and AKR (aldo-keto reductase). S-reticuline catalyzed by DRS (1,2-dehydroreticuline synthase) forming 1,2-dehydroreticuline, while the R-reticuline product is catalyzed by DRR (1,2-dehydroreticuline reductase) coming from AKR domain of epimerase [44]. During this pathway, another P450 CYP719B1facilitate the oxidative C-C bond coupling and the rearrangement of R-reticuline during the conversion of R-reticuline into salutaridine and finally into Morphine [57].…”
Section: Figurementioning
confidence: 99%
“…In a comparison of the metabolic pathways for 21 drugs and other compounds in the rat and man (4Y), the rat provided a "good" metabolic model for man with only 4 compounds and was a "poor" or "invalid" model (metabolic pathways quite different) with 15 of the compounds studied (Table II). However, the rhesus monkey or marmoset provided "good" metabolic models for man with 16 The rate, extent, mechanisms, and products of metabolism are inevitably linked to the expression of toxic action, and a clear definition of pesticide biotransformation is often a necessary prerequisite to understanding mechanisms of toxicity and to the formulation of approaches for assessment and management of potentially undesired toxic effects.…”
Section: Pesticide Conjugatesmentioning
confidence: 99%